Fashion and the Urban Teenager Behavior at Shopping Malls in Medellin (2019)
This article presents the results of a qualitative research that pretends to understand how the teen consumers behave and their relationship with fashion at shopping malls. Specifically, the paper describes the clothing usage of teenagers at shopping malls, the activities young people develop at these shopping environments and the present elements in the initial stages of the fashion purchase process. This research uses the technique of participant observation, complemented by short and in-depth interviews. The study confirms the social nature of teenagers’ behavior at shopping malls, giving high importance to group belonging. Lonely teenagers are not found and their behavior depends on the group size. This might explain the high frequency of visits to shopping malls, since these are places positioned in most teenagers’ mind as “meeting points”.